Impact of Oral Hygiene Discontinuation on Supragingival and Salivary Microbiomes. (January 2018) - Belstrøm, D.; Sembler-Møller, M.L.; Grande, M.A.; Kirkby, N.; Cotton, S.L.; Paster, B.J.; Twetman, S.; Holmstrup, P.
The purpose of the present study was to characterize and compare supragingival and salivary microbiotas during a 10-d period of oral hygiene discontinuation. We tested the hypothesis that the composition of the salivary microbiota will reflect local microbial changes associated with accumulated biofilm formation and maturation. Pooled supragingival plaque ( n = 145) and stimulated saliva ( n = 145) samples were collected and plaque and gingival indices were recorded from 29 orally healthy individuals at baseline, during oral hygiene discontinuation (days 4, 7, and 10), and 14 d after resumption of oral hygiene. Supragingival and salivary microbiotas were processed by next-generation sequencing (Human Oral Microbe Identification using Next Generation Sequencing) and microbial community profiles were compared. Microbial composition of supragingival plaque samples collected after 4, 7, and 10 d of oral hygiene discontinuation, as well as 14 d after reuptake of oral hygiene, differed significantly from baseline samples, by a 3-fold increase in relative abundance Leptotrichia species and a 2-fold decrease in Streptococcus species (adjusted P < 0.01). In saliva samples, a significant increase in relative abundance of Leptotrichia species (adjusted P < 0.01) was evident at day 7 but completely reversed 14 d after resumption of oral hygiene. While the salivary microbiota was resistant to accumulated local biofilm formation, data from this study showed that compositional changes of supragingival microbiotas were not reversed 14 d after resumption of oral hygiene, despite the restoration of plaque to baseline levels. (ClinicalTrials.gov UCPH_OI_002, NCT02913235). Knowledge Transfer Statement: Data from this study showed compositional changes of supragingival microbiotas as a consequence of a 10-d period of oral hygiene discontinuation, that was not reversed 14 d after resumption of oral hygiene. Notably, oral hygiene discontinuation was associated with a significant increase in relative abundance of potential cariogenic Leptotrichia species and a decrease in Streptococcus species. Thus, findings from this study highlight the necessity of regular oral hygiene in the maintenance of oral homeostasis.